2020
DOI: 10.3390/su12125067
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Fitness Center Business Sustainability: A Qualitative Vision

Abstract: The growing interest in fitness services is demanding optimal service management and operation. This research aims to identify the best practices in fitness center management for increasing customer engagement and for long-term stability and sustainability of the business. A qualitative approach through 23 semi-structured interviews to fitness center managers was performed in Spain, covering private centers with diverse business models (7 low-cost, 13 mid-market, and 3 premium). The managers were asked about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 46 publications
2
41
0
5
Order By: Relevance
“…In general terms, having carried out the IPMA the results showed that ambient conditions are the most valuable variable to increase the loyalty of consumers in fitness centers. Precisely, this aspect would be related to music [ 79 ], the colors used and the noise level [ 80 ], or cleanliness as suggested by Kim et al (2016) [ 9 ] and León-Quismondo et al (2020) [ 81 ]. This fact coincides with the works of Vilnai-Yavetz and Gilboa (2010), Bester (2012), and the study by Lee and Kim (2014) who concluded that a neglected environmental environment could decisively negatively influence a consumer’s loyalty [ 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general terms, having carried out the IPMA the results showed that ambient conditions are the most valuable variable to increase the loyalty of consumers in fitness centers. Precisely, this aspect would be related to music [ 79 ], the colors used and the noise level [ 80 ], or cleanliness as suggested by Kim et al (2016) [ 9 ] and León-Quismondo et al (2020) [ 81 ]. This fact coincides with the works of Vilnai-Yavetz and Gilboa (2010), Bester (2012), and the study by Lee and Kim (2014) who concluded that a neglected environmental environment could decisively negatively influence a consumer’s loyalty [ 82 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have focused on studying the impact of the shape and technical characteristics of sports materials on physical performance [ 46 , 47 ], with a focus on the efficiency of motor and technical capacities [ 48 , 49 ]. The specialists in prophylaxis and physiotherapy focused on adapting the use of materials in the process of motor recovery and functional rehabilitation, depending on the technical characteristics and the individual and pathological particularities of the subjects [ 50 , 51 , 52 ]. The trend of using different sports and fitness materials is becoming increasingly obvious, and their area of use is increasingly extensive, including fitness centers and sport activities.…”
Section: Discussionmentioning
confidence: 99%
“…There is no direct correlation between fitness centers with a higher Walk Score ® and wider opening hours. Good management practices encourage sport facilities managers to reinforce their company strengths [32]. Therefore, for fitness centers whose location is considered a strength, maximizing and enlarging opening hours contributes to maximizing this strength.…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, several authors have raised the importance of the evaluation of fitness services, meaning a detailed analysis of the provided service that contributes to making managerial actions more precise. Additionally, authors have examined specific business models based on price [31] or the analysis of the importance and performance of different services and management decisions [32]. For this purpose, after the literature review, a possible relationship between the Walk Score ® and different variables such as prices, opening hours, and specific services at fitness centers is considered, depending on the city district and its walkability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation